Electrocardiographic Voltages: Normal Criteria for a Pediatric Population in Cuba - Elibet Chávez González; Emilio González Rodríguez; María del Carmen Llanes Camacho; Raimundo Carmona Puerta; Yosvany García Nóbrega; Merlin Garí Llanes (Medisur)
Background: the electrocardiogram is a simple cardiac evaluation method. Even more, it is the simplest complementary tool in cardiology and its interpretation is always of clinical interest. Objective: to describe the normal criteria for electrocardiographic voltages in a Cuban pediatric population. Methods: a descriptive study was conducted. The sample included 376 students in third, fourth and fifth grade from two elementary schools in the Municipality of Santa Clara, Villa Clara. All patients underwent 12-derivation surface, two-dimensional and M-mode echocardiographies. Left ventricular mass index was calculated according to the 95th percentile. Electrocardiogram voltages were measured and the 98th percentile was selected for each of these values, so that voltage criteria in a pediatric population would emerge. Results: size, size 2,7and age did not differ significantly according to sex; the 95th percentile of left ventricular mass index was 48.0 g / m 2, 7. Significant differences for average voltages were only found in SV1 and SV2. Conclusions: it is necessary to establish cutoff points for left ventricular mass index and voltage criteria for left ventricular hypertrophy in different populations, so that biases are eliminated in future samples selection.